A comparison of keying methods in the Hubenko architecture as applied to wireless sensor networks. (2nd June 2010) - Antosh, Cory J.; Mullins, Barry E.; Baldwin, Rusty O.; Raines, Richard A.
As wireless sensor networks (WSNs) become more prolific, the need to secure their communications increases. This paper describes the impact of using three rekey protocols – pair-wise, hierarchical and secure lock – for a WSN using the Hubenko architecture. The performance of each protocol is evaluated within a Matlab simulation to determine the impact of each on the number of bits transmitted, total power required and memory occupied. Results indicate that the Hubenko architecture does significantly increase system performance with the selection of the rekey protocol being driven by the size of the network and available memory. In terms of the number of bits transmitted, secure lock is the most efficient for small networks, while hierarchical is best for networks of 500 or more nodes. In terms of memory used, secure lock performs best for small networks, while hierarchical is best for networks with 100 or more nodes.